Recommendations for excision following core needle biopsy of the breast: a contemporary evaluation of the literature. Issue 1 (January 2016) - Calhoun, Benjamin C; Collins, Laura C
Abstract : Pathologists frequently encounter non‐malignant histological findings in percutaneous core needle biopsies (CNBs). Standards for the management of patients with lesions such as atypical ductal hyperplasia, atypical lobular hyperplasia, and lobular carcinoma in situ, as well as other benign lesions, are not well defined, and recommendations for surgical biopsy or continued clinical and radiological follow‐up are inconsistent. The frequency with which these lesions are 'upgraded' to carcinoma in excision specimens is widely variable in the literature. Many CNB studies lack careful radiological–pathological correlation, clear criteria for excision, and clinical follow‐up for patients on whom excision was not performed. This review of the recent literature emphasizes studies with radiological–pathological correlation, with the goal of developing a contemporary, evidence‐based approach to the management of non‐malignant lesions of the breast diagnosed on CNB. The data supporting an emerging consensus on which lesions may not require excision are highlighted. The management of non‐malignant lesions diagnosed on magnetic resonance imaging‐guided CNB is also discussed.